Migrants’ Discourse Formation using Historical Narratives in Lithuanian News Portals during the Year 2015 - Popovaitė, Virginija (Lietuvos istorijos studijos, 2018)
[article in Lithuanian; abstract and key words in English] In the year 2015 Europe was facing what appeared to be the worst migration crisis since World War II. Its coverage in Lithuanian media has spurred different voices to reach out for the audience: the country was facing the New Other, with whom there were no shared memories or experiences. Certain historic narratives and their motifs were invoked into discussion in order to embrace certain attitudes or actions while trying to comprehend the ongoing crisis: The Grand Duchy of Lithuania, World War II and Soviet Occupation. The two-staged research was done in order to reveal how historical narratives were used to comprehend the possible newcomers and project outcomes of positioning migrants. 7 major news portals were used as a source of research, chosen by its importance or audience reach on national and regional levels with key words “pabėgėlis” (refugee), “migrantas” (migrant), “nelegalas” (illegal person), “bėglys” (fugitive), “atbėgėlis” (arrival). At the first stage, trending discourses and keywords were revealed, while during the 2nd the usage of historical narratives while positioning the newcomers was analysed. Data is divided according to historic moments that were used. Matrices of positioning self-other, attributing the agency and the outcome with possible suggestion of what to expect from the Others and how to comprehend them were drawn. Results revealed that the multicultural GDL narrative was used for distancing and traumatic WWII and Soviet occupation narrations were the ones to bring migrants closer for a momentary lapse. Variety of historical passages highlights the ongoing struggle of creating the face of the New other. Narrations are done in homogenic manner instead of charging stories with ethnically diverse experiences, resulting in not giving migrants an historical time.